A commercial autogenous injection vaccine protects ballan wrasse (Labrus bergylta, Ascanius) against Aeromonas salmonicida vapA type V. Issue 107 (December 2020) - Ramirez-Paredes, J.G.; Verner-Jeffreys, D.W.; Papadopoulou, A.; Monaghan, S.J.; Smith, L.; Haydon, D.; Wallis, T.S.; Davie, A.; Adams, A.; Migaud, H.
Abstract: Atypical Aeromonas salmonicida (a As ) and Vibrionaceae related species are bacteria routinely recovered from diseased ballan wrasse used as cleaner fish in the Atlantic salmon farming industry. Autogenous (i.e. farm specific inactivated) multivalent vaccines formulated from these microorganisms are widely used to protect farmed wrasse despite limited experimental proof that they are primary pathogens. In this study, the components of a commercial multivalent injection vaccine containing four strains of Aeromonas salmonicida and one strain of Vibrio splendidus previously isolated from ballan wrasse in Scotland, were tested for infectivity, pathogenicity and virulence via intra peritoneal injection at pre-deployment size (25–50 g) and the efficacy of the vaccine for protection against a As assessed. Injection with 3.5 × 10 9, 8 × 10 9 1.8 × 10 9 and 5 × 10 9  cfu/fish of Vibrio splendidus, V. ichthyoenteri, Aliivibrio logeii and A. salmonicida, respectively, did not cause significant mortalities, lesions or clinical signs after a period of 14 days. IP injection with both a As and Photobacterium indicum successfully reproduced the clinical signs and internal lesions observed during natural outbreaks of the disease. Differences in virulence (LD50 at day 8-post infection of 3.6 × 10 6  cfu/fish and 1.6 × 10 7  cfu/fish) were observed for two a As vapA type V isolates. In addition, the LD50 for Photobacterium indicum was 2.2 × 10 7  cfu/fish. The autogenous vaccine was highly protective against the two a As vapA type V isolates after 700-degree days of immunisation. The RPSFINAL values for the first isolate were 95 and 91% at 1 × 10 6  cfu/fish and 1 × 10 7  cfu/fish, respectively, and 79% at 1 × 10 7  cfu/fish for the second isolate tested. In addition, significantly higher anti a As seral antibodies (IgM), were detected by ELISA in vaccinated fish in contrast with control (mock vaccinated) fish. These results suggest wrasse can be effectively immunised and protected against a As infection by injection with oil adjuvanted vaccines prepared with inactivated homologous isolates. Highlights: Intraperitoneal challenge model developed for ballan wrasse against Aeromonas salmonicida vapA type V. Vaccine provided high protection in ballan wrasse against homologous a As vapA type V strains (RPS 79–95%). Specific serum antibodies (IgM) were detected in vaccinated fish.